Knowledge and Practice Regarding Toilet Training Among Mothers of Toddler at Sundarharaicha, Morang, Nepal (Purbanchal University Health Journal, 2024)
Introduction: Toilet training is a significant milestone in a child's development involving both physiological and psychological readiness. It is the process of teaching toddler to control the bowel and bladder. Mother plays a crucial role in the toilet training process.Objective: The objective of the study was to assess the knowledge and practice regarding toilet training among mothers of toddler at Sundarharaicha, Morang, Nepal.Method: A descriptive cross-sectional study was conducted at Sundarharaicha, Morang, Nepal from August 2022 to July 2023 involving 215 mothers of toddler aged 15 to 36 months selected through convenience sampling. Purbanchal University School of Health Sciences- Institutional Review Committee (PUSHS-IRC) granted ethical clearance and informed consent were taken from study participants. Data were collected through interview using a questionnaire and checklist. Descriptive and inferential statistics were employed for data analysis using SPSS version 21. P value